Anxiety levels in football professionals and athletes before and after COVID-19 vaccination - Natã Sant’anna Esteves; Diego Ignacio Valenzuela Pérez; Michele Andrade de Brito; Rodrigo Cunha de Mello Pedreiro; Reinaldo Oliveira Paizante; Esteban Aedo Muñoz; Ciro José Brito; Bianca Miarka (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction. This study explored the impact of COVID-19 vaccination on anxiety levels among football professionals and athletes, emphasizing the relationship between vaccination, mental health, and performance.